Selective Activation of Basal Forebrain Cholinergic Neurons Attenuates Polymicrobial Sepsis–Induced Inflammation via the Cholinergic Anti-Inflammatory Pathway. Issue 10 (October 2017) - Zhai, Qian; Lai, Dengming; Cui, Ping; Zhou, Rui; Chen, Qixing; Hou, Jinchao; Su, Yunting; Pan, Libiao; Ye, Hui; Zhao, Jing-Wei; Fang, Xiangming
Abstract : Objectives: Basal forebrain cholinergic neurons are proposed as a major neuromodulatory system in inflammatory modulation. However, the function of basal forebrain cholinergic neurons in sepsis is unknown, and the neural pathways underlying cholinergic anti-inflammation remain unexplored. Design: Animal research. Setting: University research laboratory. Subjects: Male wild-type C57BL/6 mice and ChAT-ChR2-EYFP (ChAT) transgenic mice. Interventions: The cholinergic neuronal activity of the basal forebrain was manipulated optogenetically. Cecal ligation and puncture was produced to induce sepsis. Left cervical vagotomy and 6-hydroxydopamine injection to the spleen were used. Measurements and Main Results: Photostimulation of basal forebrain cholinergic neurons induced a significant decrease in the levels of tumor necrosis factor-α and interleukin-6 in the serum and spleen. When cecal ligation and puncture was combined with left cervical vagotomy in photostimulated ChAT mice, these reductions in tumor necrosis factor-α and interleukin-6 were partly reversed. Furthermore, photostimulating basal forebrain cholinergic neurons induced a large increase in c-Fos expression in the basal forebrain, the dorsal motor nucleus of the vagus, and the ventral part of the solitary nucleus. Among them, 35.2% were tyrosine hydroxylase positive neurons. Furthermore, chemical denervation showed that dopaminergic neurotransmission to the spleen is indispensable for the anti-inflammation. Conclusions: These results are the first to demonstrate that selectively activating basal forebrain cholinergic neurons is sufficient to attenuate systemic inflammation in sepsis. Specifically, photostimulation of basal forebrain cholinergic neurons activated dopaminergic neurons in dorsal motor nucleus of the vagus/ventral part of the solitary nucleus, and this dopaminergic efferent signal was further transmitted by the vagus nerve to the spleen. This cholinergic-to-dopaminergic neural circuitry, connecting central cholinergic neurons to the peripheral organ, might have mediated the anti-inflammatory effect in sepsis. Abstract : Supplemental Digital Content is available in the text.